Implementation of Low-Cost Laboratory in Education: A Systematic Literature Review - Fajrin, Suryadi; Hakim, Dadang Lukman (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2023)
The availability of educational facilities is still a problem in many countries. Inadequate laboratory equipment will affect student learning outcomes and the quality of graduates. Therefore, many studies have developed low-cost laboratories as an alternative solution. This article aims to study the development of low-cost laboratories and their implementation in learning. This study used the systematic literature review (SLR) method. The articles used in this study were published from 2017–2021 and obtained from the IEEE Xplore database. After the papers were accepted, we were selected using inclusion and exclusion criteria. Thirty-two articles were used. The results show that a low-cost laboratory can be an alternative solution to the high price of commercial equipment and a learning tool to improve learning outcomes. The methods used in implementing low-cost laboratories are design, research and development, and experimentation. Using low-cost laboratories in learning activities improves the quality of learning outcomes.